Transportation Land Fairness : Comparison Enforcement of Over Dimension Over Loading in Indonesia, Singapore and Malaysia - Vicki Dwi Purnomo; Sigit Irianto; Sri Retno Widyorini (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
Over Dimension Over Loading remains a persistent problem in land transportation systems as it directly contributes to traffic accidents, road infrastructure deterioration, and unfair competition within the logistics industry. Despite regulatory frameworks designed to control vehicle dimensions and load limits, violations continue to occur in many countries, indicating a gap between legal provisions and enforcement practices. This study aims to examine how ODOL regulations are formulated and enforced in Indonesia, Malaysia, and Singapore, and to identify the institutional and regulatory factors influencing their effectiveness. Using a comparative normative legal approach combined with qualitative analysis of regulatory frameworks, enforcement mechanisms, and institutional practices, the study analyzes statutory provisions, policy documents, and enforcement data from the three jurisdictions. The findings reveal that Indonesia’s Zero ODOL policy faces significant challenges, including uneven enforcement infrastructure, high levels of non-compliance, and limited inter-agency coordination. Malaysia has established a relatively strong legal framework and intensive enforcement operations through the Road Transport Department, yet extreme overloading cases remain frequent, particularly within port-related distribution chains and highway transport corridors. In contrast, Singapore demonstrates a more integrated regulatory model supported by strict permit systems, advanced monitoring mechanisms, and coordinated enforcement, although certain technical compliance issues such as speed limiter installation still occur. The comparative analysis highlights that effective ODOL control requires not only comprehensive regulations but also robust enforcement capacity, technological monitoring systems, and institutional coordination. This research contributes academically by offering a comparative regulatory model for ODOL governance and proposes policy directions for strengthening enforcement infrastructure, harmonizing regional transport regulations, and encouraging compliance within the logistics sector to promote safer and more sustainable land transportation systems.